Genotypic Differences Among Scions and Rootstocks Involved with Oxidative Damage and Ionic Toxicity in Cashew Plants Under Salinity - Eugênio Silva Araújo Júnior; Anselmo Ferreira Silva; Josemir Moura Maia; Elania Freire da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Hugo Rafael Bentzen Santos; Carlos Alberto Vieira Souza; Adriano do Nascimento Simões; Eduardo Souza; Sérgio Luiz Ferreira-Silva (Horticulturae)
The aim of this study was to evaluate the influence of scion/rootstock genotypes on ionic toxicity, oxidative damage, and photosynthesis in cashew plants subjected to salt stress. Scion/rootstock combinations (CCP 76/CCP 76, CCP 76/CCP 09, CCP 09/CCP 09 and CCP 09/CCP 76) were obtained by reciprocal grafting between two genotypes (CCP 76 and CCP 09) of dwarf cashew and subjected to increased NaCl (0, 50 and 100 mM) for 30 days. Plants with CCP 76 scions had higher leaf fresh weights compared to plants with CCP 09 scions in both moderate (50 mM)- and high (100 mM)-salinity conditions. Under moderate levels of salinity, CCP 76 scions showed lower stomatal conductance, which is associated with weaker leaf toxicity symptoms, as well as lower Na+ content and higher K+ content in the leaves. Thus, the better foliar exclusion of Na+ by CCP 76 scions can be attributed to greater stomatal control, which allows for better growth and sufficient foliar K+ nutrition to mitigate foliar toxicity. Under high levels of salinity, a reduction in net photosynthesis occurred in all scion/rootstock combinations, which was apparently due to stomatal and non-stomatal restrictions. The activities of the oxidative enzymes (superoxide dismutase—SOD; ascorbate peroxidase—APX; and phenol peroxidase—POD) were little influenced by salinity, while there was a significant increase in the non-enzymatic antioxidants ascorbate (AsA) and glutathione (GSH). In addition, a reduction in photochemical activity was observed under saline conditions, suggesting that photosystems possess a potential protective mechanism. It was observed that the stomatal closure exhibited by the CCP 76 scion genotype may exert relative control over the flow of Na+ to the shoots under salt stress conditions. Taken together, the data show that, in the two genotypes evaluated, oxidative protection was more associated with reduced photochemical activity and higher levels of non-enzymatic antioxidants (AsA and GSH) than it was with the SOD-APX-POD enzymatic system.